The Insect Ortholog of the Human Orphan Cytokine Receptor CRLF3 Is a Neuroprotective Erythropoietin Receptor - Hahn, Nina; Knorr, Debbra Y.; Liebig, Johannes; Wüstefeld, Liane; Peters, Karsten; Büscher, Marita; Bucher, Gregor; Ehrenreich, Hannelore; Heinrich, Ralf (Frontiers in Molecular Neuroscience, 2017)
The cytokine erythropoietin (Epo) mediates various cell homeostatic responses to environmental challenges and pathological insults. While stimulation of vertebrate erythrocyte production is mediated by homodimeric “classical” erythropoietin receptors, alternative receptors are involved in neuroprotection. However, their identity remains enigmatic due to complex cytokine ligand and receptor interactions and conflicting experimental results. Besides the classical erythropoietin receptor, the family of type I cytokine receptors also includes the poorly characterised orphan cytokine receptor-like factor 3 (CRLF3) present in vertebrates including human and various insect species. By making use of the more simple genetic makeup of insect model systems, we studied whether CRLF3 is a neuroprotective erythropoietin receptor in animals. We identified a single orthologue of CRLF3 in the beetle Tribolium castaneum, and established protocols for primary neuronal cell cultures from Tribolium brains and efficient in vitro RNA interference. Recombinant human Epo as well as the non-erythropoietic Epo splice variant EV-3 increased the survival of serum-deprived brain neurons, confirming the previously described neuroprotective effect of Epo in insects. Moreover, Epo completely prevented hypoxia-induced apoptotic cell death of primary neuronal cultures. Knockdown of CRLF3 expression by RNA interference with two different double stranded RNA fragments abolished the neuroprotective effect of Epo, indicating that CRLF3 is a crucial component of the insect Epo-responsive receptor. This suggests that a common urbilaterian ancestor of the orphan human and insect cytokine receptor CRLF3 served as a neuroprotective receptor for an Epo-like cytokine. Our work also suggests that vertebrate CRLF3, like its insect orthologue, might represent a tissue protection-mediating receptor.